Navigating Theory and Practice Through Evaluation Fieldwork: Experiences of Novice Evaluation Practitioners. (December 2017) - Chouinard, Jill Anne; Boyce, Ayesha S.; Hicks, Juanita; Jones, Jennie; Long, Justin; Pitts, Robyn; Stockdale, Myrah
To explore the relationship between theory and practice in evaluation, we focus on the perspectives and experiences of student evaluators, as they move from the classroom to an engagement with the social, political, and cultural dynamics of evaluation in the field. Through reflective journals, postcourse interviews, and facilitated group discussions, we involve students in critical thinking around the relationship between evaluation theory and practice, which for many was unexpectedly tumultuous and contextually dynamic and complex. In our exploration, we are guided by the following questions: How do novice practitioners navigate between the world of the classroom and the world of practice? What informs their evaluation practice? More specifically, how can we understand the relationship between theory and practice in evaluation? A thematic analysis leads to three interconnected themes. We conclude with implications for thinking about the relationship between theory and practice in evaluation.